The state as an actor in religion policy : policy cycle and governance perspectives on institutionalized religion - Martino, Maria Grazia (Springer Fachmedien Wiesbaden Imprint: Springer VS, 2015)
Churches and religious communities are actors from civil society. The state sets the framework for their activities, first and foremost by formal legal acts in ecclesiastical law. Besides this field of law, religion policy has increasingly developed into a policy field of its own. Which incentives and steering tools used by the state cause which kind of behavior, which role in society and which self-understanding among churches and religious communities? This edited volume answers these questions. Maria Grazia Martino and her contributing authors highlight the different solutions found by European countries with different ecclesiastical law systems, different distributions of Christian denominations and different percentages of Muslim immigrants: Germany, Switzerland, France, Sweden, Italy and Greece. Contents Germany and Religion, Does Islam belong to Germany? Switzerland: No Religious Peace without Public Arrangements Denominational Influence on Religion Policy after the State Church? Dealing with Religious Diversity: Aims and Realities of Religious Education in Sweden European Turks in-between Local and Transnational Islamic Networks Target Groups Scientists and students in the field of political sciences, especially religion The Editor Dr. Maria Grazia Martino studied Political Science at the universities of Constance and Tübingen. Since 2013, she holds a lecturer position for Political Theory at the Otto Suhr Institute of Political Science at Freie Universität Berlin.